Removal of Bentazon and Metalaxyl pesticides from aqueous solutions by using chestnut shells: Process optimization by experimental design, adsorption kinetics and isotherm analysis - Diler, Baris; Apar, Dilek Kilic (SCIENTIFIC PUBL-INDIA, 2019)
Usability of agricultural waste chestnut shells as adsorbent for the removal of Bentazon and Metalaxyl pesticides from aqueous solutions was investigated. By using Box-Behnken experimental design, effects of pH (2.0, 3.5 and 5.0), adsorbent concentration (1, 2 and 3 g/50 ml), pesticide concentration (25, 50 and 75 mg/L) and processing time (40, 80 and 120 min) on adsorption were investigated and optimizations of the adsorption processes were performed. At the determined optimum conditions 85.1% Bentazon and 66.1% Metalaxyl removals were obtained. Also model equations that shows the effects of process parameters on adsorption were obtained. As a result of the analyzing the data obtained from the kinetics and equilibrium studies it was determined that the adsorption of Bentazon and Metalaxyl with chestnut shells could be represented with pseudo-second kinetic and Freundlich isotherm models. The results obtained from this study suggested that the agricultural waste chestnut shells could be used as cheap and easily accessible adsorbent for the removal of pesticides from waste waters.
Keywords: Bentazon; Metalaxyl; adsorption; experimental design; modelling; ACTIVATED CARBON; EFFICIENCY; Chemistry